Living by the clock of the book: religious observance enhances circadian stability and reduces social jetlag in older adults, a cross-sectional study - Daria Zarina; Adi Berger; Pavel Fishbein; Vadim Tkachev; Maria Korman (BMC Public Health)
Abstract Background Religious practices often structure daily behavior, yet their role in shaping sleep–wake patterns remains underexplored. While stable schedules and socially reinforced habits are known to support circadian alignment and sleep quality, few studies have examined religious observance as a behavioral framework that promotes sleep health in older adults. This study investigated whether Jewish religious lifestyle, particularly Sabbath observance, affects habitual sleep–wake patterns in late adulthood. Methods A cross-sectional field study was conducted among 473 community-dwelling Israeli Jewish older adults (median age 69 [range 60–88]; 74.6% female; 41.9% engaged in regular work or study). Data were collected between May 2022 and February 2023 via an anonymous self-administered online survey (CLISEF), which included validated questionnaires assessing sleep behaviors, chronotype and daytime sleepiness (ultra-short Munich ChronoType Questionnaire, MCTQ; and Epworth Sleepiness Scale, ESS), and items to report subjective sleep quality, napping habits, and screen exposure at bedtime. Results Religious participants (n = 274) reported a unique pattern of sleep habits in comparison to their Secular peers (n = 199): they had on average an earlier chronotype (02:53 ± 01:02 vs. 03:13 ± 01:11, midsleep time on free days), longer sleep duration on free days (Sabbath) (442.7 ± 77.0 vs. 424.8 ± 76.6, min) and lower social jetlag (14.1 ± 39.6 vs. 25.7 ± 37.9, min). These differences stemmed from the group-specific patterns of sleep timing during free days (Sabbath) relative to workdays. While the Religious group slightly but significantly advanced sleep onset times on Sabbath (∆=-9 min), the Secular group significantly delayed their sleep onset times (∆=16 min). Both groups delayed sleep offset on Sabbath (∆=32 min and ∆=29 min). Additionally, the religious participants who practice day-time napping reported longer naps. No significant differences between Religious and Secular groups in subjective sleep quality, sleep latency, nighttime awakening patterns and habits of alarm clock use and screen exposure after bedtime were observed. Conclusions These findings suggest that Jewish religious observance contributes to more consistent sleep-wake behaviors and earlier chronotype in older adults, emphasizing the broad relevance of sleep timing regularity for promoting daily habits that may be adopted beyond specific religious or spiritual contexts.